2023
DOI: 10.1080/15548627.2022.2160564
|View full text |Cite
|
Sign up to set email alerts
|

The chaperone-assisted selective autophagy complex dynamics and dysfunctions

Abstract: Each protein must be synthesized with the correct amino acid sequence, folded into its native structure, and transported to a relevant subcellular location and protein complex. If any of these steps fail, the cell has the capacity to break down aberrant proteins to maintain protein homeostasis (also called proteostasis). All cells possess a set of well-characterized protein quality control systems to minimize protein misfolding and the damage it might cause. Autophagy, a conserved pathway for the degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 267 publications
0
26
0
Order By: Relevance
“…Thus, our observation that HDAC6 pS22 is enriched within Lewy bodies is consistent with the constituent components of Lewy bodies having been trafficked there via the microtubule network. Previous observations of aggresomes indicate they are enriched for filamentous proteins that form a cage reminiscent of those previously described for Lewy bodies [22, 35]. Therefore, there are striking similarities between Lewy bodies and aggresomes, suggesting the formation of Lewy bodies is a deliberate response by neurons to a stressor.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, our observation that HDAC6 pS22 is enriched within Lewy bodies is consistent with the constituent components of Lewy bodies having been trafficked there via the microtubule network. Previous observations of aggresomes indicate they are enriched for filamentous proteins that form a cage reminiscent of those previously described for Lewy bodies [22, 35]. Therefore, there are striking similarities between Lewy bodies and aggresomes, suggesting the formation of Lewy bodies is a deliberate response by neurons to a stressor.…”
Section: Discussionmentioning
confidence: 54%
“…As a previous study has reported mitochondria-enriched aggresomal structures in the context of mitophagy dysfunction, the present findings could be consistent with the accumulation of autophagic cargo due to α-synuclein aggregation causing autophagy dysfunction, from which the formation of a modified aggresome termed a Lewy body is a compensatory process to encapsulate autophagic cargo [37]. An alternative explanation is that α-synuclein aggregates are translocated to aggresomes, and that the presence of autophagic markers within Lewy bodies as presently reported is due to aggregates being trafficked within autophagosomes to the aggresome, as has been reported for other misfolded proteins [35]. Furthermore, the presence of autophagic mitochondria could be due to the presence of α-synuclein aggregates in damaged mitochondria, as has also been reported previously [38].…”
Section: Discussionmentioning
confidence: 94%
“…These Classes are “pre-initiation autophagy signaling”; “autophagophore initiation and elongation”; “autophagy substrate selection”; “autophagosome closure, maturation, and lysosome fusion”; “lysosomal catabolism”; and “autophagic lysosome reformation”. The remaining classes are “autophagy gene expression”, which comprises the transcription factors and transcriptional and translational regulators that control the expression of autophagy genes; “chaperone directed autophagy”, which includes components involved in chaperone-mediated autophagy 66 and chaperone assisted selective autophagy 67 ; and “specific function in autophagy unknown”, a small Class that contains components that clearly affect autophagy but through mechanisms that are not yet known. The Groups, Types, and Subtypes further specify a component’s function within the processes denoted by their Class.…”
Section: Resultsmentioning
confidence: 99%
“…Several proteins participate in selective autophagy, such as TAR DNA-binding protein 43 (TDP43), glucocerebrosidase (GBA), presenilin 1 (PSEN1), ATPase cation transporter 13A2 (ATP13A2), and superoxide dismutase-1 (SOD1) [ 29 ]. Selective autophagy processes contain proteins and specialized autophagic receptors which identify the cargo, generally mediated via cargo ubiquitination [ 30 ]. Through its interaction with a scaffold protein, the receptor either binds to cargoes or may be an integral component of these cargoes, connecting them to the autophagy machinery in the cell [ 31 ].…”
Section: Mechanism Of Autophagy Pathwaysmentioning
confidence: 99%